Employment Disputes and Industrial Relations in Nigeria: The Role of Alternative Dispute Resolution - Adebayo, Mahmud Kayode; Olokooba, Saka (NIU Journal of Humanities, 2018)
Disputes are stubborn fact of organizational life. Although disputes are familiar part of our experience in organizations, their value and centrality to organizational theory and functioning has waxed and waned as a result of changing winds of managerial ideology and theory. The landscape of employment disputes resolution has been transformed by the development of alternative dispute resolution. This paper is a review of comprehensive survey of the growing role of alternative dispute resolution in employment disputes and industrial relation. It examines the use of alternative dispute resolution as a means of settling individual workplace disputes; the methods of conciliation, mediation and arbitration; the trends in alternative dispute resolution, and concludes with an advocacy of alternative dispute resolution as a more positive, speedy and cost effective alternative to court proceedings.   Keywords : Disputes, Employment, Resolution, Alternatives, Mediation, Conciliation, Arbitration.